Effects of Malaysian Cocoa Powder Consumption on Biochemical Parameters Status of Healthy Subjects at Universiti Putra Malaysia, Serdang - Muhammad Alinafiah, Suryati (2011)
In most of developing countries, cardiovascular disease (CVD) will be the leading cause of death worldwide. By the year of 2030, almost 23.6 million people will die from CVD, mainly heart diseases and stroke, which also representing 29% of all global health. Dietary intervention revealed that the plants-derived food is negatively correlated with the risk of CVD. The consumption of cocoa (Theobrama cacao L) and its products has been often hypothesized to reduce the cardiovascular risk due to their polyphenols and antioxidant content. Polyphenols is a phytochemical that could play important role in attenuating the development of non-communicable diseases such as diabetes, atherosclerosis, cardiovascular disease, rheumatoid arthritis, ageing and certain cancers. Cocoa powder is rich in polyphenols compound compared to other food products. Malaysian cocoa beans have been reported to contain the highest phenolic content compared to Sulawesian, Ghanaian and Ivorian Coast beans. Hence this study may contribute to the crucial knowledge on the health benefits of Malaysian cocoa, which believed to have positive effects on delaying the risk of cardiovascular diseases. This cross over study was conducted to investigate the effect of Malaysian cocoa beverage (CB) consumption on biochemical parameters among healthy subjects in UPM. There were 37 subjects who consisted of 20 women and 17 men aged between 25-45 years consisted of UPM staff volunteered for the study. This study was carried out for ninth weeks and the subjects were randomized into two groups; Group 1 (n=19) and Group 2 (n=18). In the first four weeks, Group 1 was a treatment group whereas Group 2 was a control group. Subjects in treatment group were assigned to receive 18 g CB (contained 1260 mg polyphenols) daily for four weeks whereas the subjects in control group did not receive any beverage to be consumed. After the washout period (1 week), Group 2 was a treatment group and Group 1 acted a control group. Ten mililiters of fasting blood of the subjects was taken to measure cardiovascular biomarkers (plasma lipid profiles, antioxidant status and enzymes, glucose level, high sensitive-CRP and malondialdehyde). Other parameters (bodyweight changes and blood pressure levels changes) were also measured. The present study observed an improvement of lipid profiles levels and antioxidant enzymes of subjects after the consumption of Malaysian cocoa powder for 4 weeks. The total cholesterol (TC) concentrations reduced significantly by 7.29% (p<0.05). The low density lipoprotein (LDL-C) and triglycerides (TG) and high density lipoprotein (HDL-C) had improved but not with significant changes at the end of the study. The present study also showed improvement in antioxidant status and enzymes of the subjects. The levels of glutathione peroxidase (GPx) increased significantly by 68.64% (p<0.05). The level of total antioxidant status (TAS) and Superoxidase Dismutase (SOD) also improved but not with significant changes between the two groups. There were no significant changes on high sensitive-CRP (hs-CRP) and melondialdehyde (MDA) of the subjects at the end of the study. Consumption of 18 g CB daily for 4 weeks had also improved blood pressure levels and caused no toxicity effects in healthy subjects. In conclusion, several improvements in biomarkers associated with cardiovascular health following consumption of CB were observed in healthy individuals involved in the study. Malaysian CB may possibly use as functional foods to help in preventing the promotion of oxidative stress linked diseases.